Enhancing the Transparency of Highly Electroactive BNCD‐MEAs. Issue 22 (18th October 2018) - Pasquarelli, Alberto; Wang, Xuemei
Abstract : This work presents a promising method for enhancing the transparency of boron‐doped nanocrystalline diamond (BNCD) microelectrodes while preserving a good level of electrical and electrochemical performances. This method is based on the combination of selective growth of diamond on a quartz carrier and the adoption of stacked delta‐doping. The overall results show similar conductivity and at the same time better transparency in comparison with bulk doped diamond, making this technology particularly suited for applications based on simultaneous fluorescence and electrochemical detection of redox active molecules released from biological samples. Abstract : This paper presents a promising method for enhancing the transparency of boron‐doped nanocrystalline diamond microelectrodes while preserving good electrical and electrochemical performances, based on combining selective growth of diamond on quartz and stacked δ‐doping. Similar conductivity and better transparency than bulk‐doped diamond make the resulting MEAs suited for simultaneous fluorescence and electrochemical detection of cell activity.